The Influence of Teachers' Digital Literacy and Media Literacy on The Quality of Learning at Raudhatul Athfal - Sri Purwati; Sukiman (Kirana Publisher (KNPub), 2024)
This study aims to analyze the influence of digital literacy and media literacy of teachers on the quality of learning in Raudhatul Atfhal, Bogor Regency. This research uses a quantitative approach with survey methods. The independent variables or independent variables in the study are digital literacy and media literacy. The variable tied to this study is the quality of learning. The population in this study of all Raudhatul athfal teachers in Bogor Regency amounted to 1,905 teachers. The probability method used in this study is stratified random sampling. From 5 sub-districts, 20 respondents were represented, so the total sample was 100 respondents. In this research, the data collection instrument is in the form of questionnaires. The data analysis technique used in this study is multiple linear regression using SPSS software. The results showed a value of R2 = 0.748, meaning that the independent variables of media literacy and digital literacy were able to increase variables related to learning quality by 74.8%. The remaining 25.2% was influenced by factors other than regression. Based on the calculation results with the SPSS program above, it appears that the r value is smaller than the level of a used, which is 0.000 or 0.000< 0.05 so that Ho is rejected and Ha is accepted. This means that there is a significant influence of digital literacy and media literacy on the quality of learning.